2022
DOI: 10.1021/acsomega.2c04729
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Printable Ionotronic Sensing Materials Based on Silk Fibroin and Soluble Plant-Derived Polyphenols

Abstract: The emergence of ionotronic materials has been recently exploited for interfacing electronics and biological tissues, improving sensing with the surrounding environment. In this paper, we investigated the synergistic effect of regenerated silk fibroin (RS) with a plant-derived polyphenol (i.e., chestnut tannin) on ionic conductivity and how water molecules play critical roles in regulating ion mobility in these materials. In particular, we observed that adding tannin to RS increases the ionic conductivity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Fibroblast and NPC morphology, confluence, and growth indicate the excellent biocompatibility of RS hybrids (Figures 5A and B). In addition, we observed that low doses of tannin were not cytotoxic to fibroblasts and NPCs, confirming their antioxidant and cytoprotective properties (32).…”
Section: Characteristics Detected and Cell Viability Characteristics ...supporting
confidence: 67%
See 1 more Smart Citation
“…Fibroblast and NPC morphology, confluence, and growth indicate the excellent biocompatibility of RS hybrids (Figures 5A and B). In addition, we observed that low doses of tannin were not cytotoxic to fibroblasts and NPCs, confirming their antioxidant and cytoprotective properties (32).…”
Section: Characteristics Detected and Cell Viability Characteristics ...supporting
confidence: 67%
“…The cells of the HepG2 line were cultured in EMEM (Eagle's minimal essential medium), with the addition of 10% heat inactivated fetal bovine serum (FBS), 1% non-essential amino acids, 1 mM sodium pyruvate, 2 mM of L-glutamine and antibiotics (100 U/mL penicillin, 100 μg/mL streptomycin). After a treatment of 24 h and one of 48 h, to evaluate the biocompatibility of these compounds, the MTT test was used (32), a test that measures cellular metabolic activity based on the reduction of a yellow tetrazolium salt (3-(4, 5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide or MTT) to purple formazan crystals by metabolically active cells. For this evaluation, the HepG2 cells were seeded in a 96-well plate at a cell density of 1 × 104 cells/well; after 24 hours, eight different dilutions of stock solutions (1 mg/mL) replaced the complete fresh medium and MTT reagent (0.5 μg/μL) was added to each well for 3 hours at 37° C.…”
Section: Characteristics Detected and Cell Viability Characteristics ...mentioning
confidence: 99%
“…As shown in Figure 7 a, the resistivity decreases as a function of relative humidity. This effect is a combination of the hygroscopic behavior of the peptide-functionalized silk and the activation of Ca 2+ ion mobility due to water absorption [ 25 ]. To investigate humidity’s effect on the electrical resistance of the MO-07/RS grid, we evaluated the change in current–voltage characteristics at different values of relative humidity (see Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Processing forms Filament, film, gel, nanofiber Film Film, nanofiber, electrostatic spinning fiber mat, SF coating Applications Tissue engineering [148], wound healing [146], drug delivery [147], tissue adhesion [156], electrochemistry [157], spinning [144] -Tissue engineering [158], drug release [159], spinning [145] 1 SF solution is difficult to gelate (D); 2 SF solution has good film-forming properties (G).…”
Section: Rsf Materials Propertiesmentioning
confidence: 99%